2010
DOI: 10.1063/1.3402329
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Test Results on Compacted and Annealed 316ln Material

Abstract: The torodial-field (TF) magnet coils for ITER are made by superconducting cable in conduit conductors (CICC) using 316LN for the conduit. Compaction of the conduit and heat treatment to react the Nb 3 Sn material are one of the main steps during manufacture of this type of conductor. Therefore a systematic investigation was done to examine the influence of compaction and heat treatment on the mechanical behavior of this material. Several 316LN tubes were deformed to smaller radii to obtain different stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The latter, combined with the effect of cold work produced during compaction and subsequent handling operations, can induce a loss of ductility at 4.2 K. Hence, it is critical to characterize the resulting level of embrittlement and to ensure that the material behavior is predominantly ductile in the stress range of interest. As the TF tube thickness ( 2 mm) is too small to enable the preparation of suitable samples for fracture toughness (K IC ) and fracture crack growth rate (FCGR) measurements, it was decided to circumvent this difficulty by implementing a specification on the maximum elongation of at least 20% below 7 K. It is also required to carry out a micrographic examination of the fracture surfaces so as to assess the extent of the dimple pattern zone, resulting from ductile fracture, and of the inter-granular surfaces, resulting from brittle fracture caused by grain boundary sensitization [99]. This is illustrated in Figure 36 which shows examples of tensile test specimens cut out from TF jacket sections after compaction, stretching and ageing.…”
Section: Jacket Sectionsmentioning
confidence: 99%
“…The latter, combined with the effect of cold work produced during compaction and subsequent handling operations, can induce a loss of ductility at 4.2 K. Hence, it is critical to characterize the resulting level of embrittlement and to ensure that the material behavior is predominantly ductile in the stress range of interest. As the TF tube thickness ( 2 mm) is too small to enable the preparation of suitable samples for fracture toughness (K IC ) and fracture crack growth rate (FCGR) measurements, it was decided to circumvent this difficulty by implementing a specification on the maximum elongation of at least 20% below 7 K. It is also required to carry out a micrographic examination of the fracture surfaces so as to assess the extent of the dimple pattern zone, resulting from ductile fracture, and of the inter-granular surfaces, resulting from brittle fracture caused by grain boundary sensitization [99]. This is illustrated in Figure 36 which shows examples of tensile test specimens cut out from TF jacket sections after compaction, stretching and ageing.…”
Section: Jacket Sectionsmentioning
confidence: 99%
“…ITER IO requires that the elongation (EL) shall be over 20%. It is found that the EL after the cold work and long-term AT is rather sensitive to its chemical composition thus it is used as the key parameter for monitoring conductor jacket production [9].…”
Section: Mechanical Tests On the Iter Tf Conductor Jacket Materialsmentioning
confidence: 99%
“…Deformation accumulated during tensile test can induce transformation of -austenite to '-martensite by movement of dislocations through slips [4]. Extensive work has been done to investigate the mechanical behavior of the 316LN SS after compaction and aging treatment [2,5,6]. However, a detailed study on the performance change of the base full-size TF conductor jacket after tensile tests at low temperature is lacking.…”
Section: Introductionmentioning
confidence: 99%